IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 5 TAHUN 2007 TENTANG PEMBERANTASAN PROSTITUSI : Studi Kasus di Desa Banjarwati Kecamatan Paciran Kabupaten Lamongan - Ayu Sri Astuti (The Republic : Journal of Constitutional Law, 2023)
Prostitution is a problem that is widespread in society in general in this modern era. Lamongan Regency is one of the areas where prostitution is carried out by commercial sex workers. In following up on this, the Lamongan Regency Regional Regulation stipulates Regional Regulation Number 5 of 2007 concerning the Eradication of Prostitution in Lamongan Regency, Banjarwati Village, Paciran District. optimal. However, even though there are Regional Government regulations, the implementation of prostitution practices in the area still continues without paying attention to existing regulations. There are regulations so that they can be implemented, and if they are not implemented well then there needs to be an evaluation of this. This research aims to answer, describe and analyze the problem formulation regarding how the Lamongan regional government implements policies in implementing Regional Regulation Number 5 of 2007 and what steps are taken in implementing these regulations in Banjarwati Village. The research method used in this research is a qualitative research method with a descriptive approach where the researcher goes directly to the field where the research object is and the research instruments used to collect data are by conducting observations, interviews and documentation. The results of this research concluded that the practice of eradicating prostitution of commercial sex workers in Lamongan district, Paciran sub-district, Banjarwati village is not optimal, the facts on the ground are that there are still a lot of prostitution practices in the area and with the steps that have been taken by law enforcers in implementing regional regulations. not maximal Keywords: Implementation; Local regulation; Prostitution